On the central limit theorems for sums of the renewal processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. О центральной предельной теореме для сумм процессов восстановления B. Grigelionis. Apie centrinę ribinę teoremą atstatymo procesų sumoms